Nonobatteries: Decreasing Size Power Sources for Growing Technologies - Lowy, Daniel A.; Patrut, Adrian (Recent Patents on Nanotechnology, 2008)
Increasing need for portable nanoelectronic devices triggers the development of dimensionally small batteries. Nanobatteries are being designed for specific applications, including computer chips, micro-electromechanical systems (such as micro-actuators, micro-instruments, or micro-robots), or nanostructured medical devices. As the size of power source should be commensurate with the device it powers, battery miniaturization is an important design challenge faced by the battery community. Further advantages of such minute batteries include the long shelf life and a quick ramp up to full power. Hence, design may enable the nanobattery to stay dormant for several years, and then getting reactivated, so that it can provide immediately a burst of high energy.
Keywords: “nanograss” tubes